Pendidikan Antikorupsi Perspektif Pedagogi Kritis - Subkhan, Edi (Integritas : Jurnal Antikorupsi, 2020)
At schools, campuses, or class-based courses, anti-corruption education seems to focus mainly on transferring theoretical knowledge that is included into various subjects. As such, anti-corruption contents and behaviors might not be substantially addressed across courses. Consequently, student acquisition of anti-corruption knowledge and behaviors are not properly assessed. Drawing on literature review method, this article examines such reports that are based on critical pedagogy. It found that critical pedagogy is relevant to bring anti-corruption learning practices into real action against corruption. Therefore, by employing critical pedagogy perspective, the learning practice will build students’ critical consciousness about the disadvantages and losses caused by corruption and how they should take into action against it properly. Based on the principles of stand-point theory, democratic attitude, contextuality, and action-oriented outlook, critical pedagogy can work as a guide for the anti-corruption education program and it could be organized collaboratively by engaging many stakeholders (inside and outside the schools) and using a cross-curricular approach.